Edukasi Penyakit Mastitis Saat Menyusui di Kantor Lurah Gantiang, Padang Panjang Timur - Nana Liana; Meta Zuliyati Oktora; Sri Nani Jelmila; Budi Yulhasfi Febrianto; Dita Hasni (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2022)
Breastfeeding or in a foreign language called breasting is the feeding of breast milk (breast milk) as a natural food provided to the baby. The breastfeeding process can be hampered due to several problems, one of which is mastitis. Mastitis in nursing mothers is an infection of breast tissue when the mother is breastfeeding, mainly occurs due to blockage of breast milk ducts by a coagulated breast milk and accompanied by bacteria that enter the breast tissue through the nipple. The incidence of mastitis is estimated to occur in the first 12 weeks to the second year of feeding. Mastitis needs to be considered because being one of the reasons for the mother to stop breastfeeding can proceed to other diseases such as breast abscesses. Lack of knowledge about mastitis and its treatment causes many mothers to detect mastitis too late and aggravate the state of mastitis. Therefore, prevention and education related to mastitis when the mother is breastfeeding is needed.This activity was held on July 29, 2022 for 3 hours and was attended by 23 mothers of reproductive age who lived in Gantiang village, Padang Panjang Timur. The results of this activity obtained differences in the average level of knowledge of participants before and after counseling. This activity has an impact on increasing public knowledge related to mastitis so that it can increase the success of breastfeeding and prevent stunting.